Long‐term follow‐up of a randomized controlled trial comparing systemic family therapy (FT‐S) added to treatment as usual (TAU) with TAU alone in adolescents with anorexia nervosa. (18th February 2022) - Godart, Nathalie; Dorard, Géraldine; Duclos, Jeanne; Curt, Florence; Kaganski, Irène; Minier, Lisa; Corcos, Maurice; Falissard, Bruno; Eisler, Ivan; Jeammet, Philippe; Berthoz, Sylvie
Abstract : Background: Randomized controlled trials showed the efficacy of family therapy for anorexia nervosa during adolescence, but studies examining its long‐term beneficial effect are still needed. This article presents the results of a 54‐month post‐randomization follow‐up of a previously reported randomized controlled trial that compared two post‐hospitalization outpatient treatment programs: Treatment As Usual alone versus Systemic Family Therapy added to Treatment As Usual. Methods: A consecutive series of 60 female adolescents with anorexia nervosa (DSM‐IV) were randomized (30 per group). During the first 18 months, in the Treatment As Usual group, subjects received a multidisciplinary treatment. In the other group, Systemic Family Therapy sessions targeting intra‐familial dynamics were added to Treatment As Usual. At 54 months, the primary outcome was defined using the Morgan and Russell global Outcome Categories (Good or Intermediate versus Poor). Secondary outcomes were the Global Outcome Assessment Schedule score, body mass index, amenorrhea, number of hospitalizations, eating disorder symptoms, psychopathological features, and family functioning. Analyses were carried out using an Intention‐To‐Treat with the Last Observation Carried Forward procedure. Data of 59/60 subjects were available. Results: At 54 months, significant effects in favor of adding Systemic Family Therapy to Treatment As Usual were shown for the Global Outcome Categories (60% of Good/Intermediate versus 31% in the control group, p = .026), mean body mass index ( p = .048), resumption of menses (70.0% vs. 40% p = .020), and mental state score ( p = .010). Family cohesion scores were lower in the Systemic Family Therapy group ( p = .040). Conclusions: Adding Systemic Family Therapy focusing on intra‐familial dynamics to a multidimensional outpatient treatment program appeared to lead to a better long‐term outcome in young women who suffered from severe anorexia nervosa during adolescence.